Conversations with John Steinbeck - Steinbeck, John, 1902-1968.; Fensch, Thomas (Jackson [Miss.] : University Press of Mississippi, 1988)
Presents more than twenty interviews with American author John Steinbeck spanning 1935-1968, and includes a chronology of his life and career.
Includes index.
Wilson's Senior High School.
Adult.
Adult
Keywords: Steinbeck, John, -- 1902-1968 -- Interviews; Steinbeck, John, -- 1902-1968 -- Interviews; Novelists, American -- 20th century -- Interviews; American novelists -- Interviews